2019
DOI: 10.2139/ssrn.3399541
|View full text |Cite
|
Sign up to set email alerts
|

Competing Mechanisms and Folk Theorems: Two Examples

Abstract: We study competing-mechanism games under exclusive competition: principals first simultaneously post mechanisms, after which agents simultaneously choose to participate and communicate with at most one principal. In this setting, which is common to competing-auction and competitive-search applications, we develop two complete-information examples that question the relevance of the folk theorems for competing-mechanism games documented in the literature. The first example shows that there can exist pure-strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…We now show that the outcome (1)-( 2) for α = 2 3 cannot be supported in any PBE of any game without signals in which principals are constrained to post standard mechanisms, irrespective of the richness of message spaces. That is, private signals are indispensable to support the outcome in ( 1)- (2).…”
Section: The Indispensability Of Private Signalsmentioning
confidence: 85%
See 2 more Smart Citations
“…We now show that the outcome (1)-( 2) for α = 2 3 cannot be supported in any PBE of any game without signals in which principals are constrained to post standard mechanisms, irrespective of the richness of message spaces. That is, private signals are indispensable to support the outcome in ( 1)- (2).…”
Section: The Indispensability Of Private Signalsmentioning
confidence: 85%
“…We now show that the outcome (1)-( 2) for α = 2 3 cannot be supported in any PBE of any game without signals in which principals are constrained to post standard mechanisms, irrespective of the richness of message spaces. That is, private signals are indispensable to support the outcome in ( 1)- (2). To this end, we consider a general competing-mechanism game without signals in which every principal j can only post a standard mechanism φ j : M j → ∆(X j ).…”
Section: The Indispensability Of Private Signalsmentioning
confidence: 85%
See 1 more Smart Citation
“…All equilibrium analyses in most applications are consistent with the notion of quasi ex-post equilibrium but their equilibria are special cases. 2 There is multiplicity of continuation equilibria tied to a quasi ex-post equilibrium. For example, consider competition between two principals.…”
Section: Introductionmentioning
confidence: 99%
“…We show that it does not have to be the case for a robust quasi ex-post equilibrium. It is shown that a robust quasi ex-post equilibrium can be understood in a way that a non-deviating principal punishes a deviating principal with a single EPIC direct mechanism re- 2 In many applications, there are no informational externalities and a non-deviating principal maintains the same dominant-strategy incentive compatible (DIC) direct mechanism on or off the path following a competing principal's deviation. Some of examples are second-price auctions with reserve price (Burdett and Sakovics (1999), McAfee (1993), Peters (1997), Peters and Severinov (1997), Virag (2010)) and fixed-prices (Burdett, Shi, and Wright (2001), Peters (1984Peters ( , 1991).…”
Section: Introductionmentioning
confidence: 99%